The Role of Health Literacy in Improving Health Outcomes: Challenges, Interventions, and Policies - Sudirman (Yayasan Sinergi Kawula Muda, 2022)
Health literacy is a critical determinant of health outcomes and disease prevention. This study systematically reviews the relationship between health literacy and health behaviors, emphasizing its role in improving adherence to preventive measures and healthcare utilization. A comprehensive literature search was conducted using PubMed, Scopus, and Google Scholar, focusing on peer-reviewed studies that examined the impact of health literacy on preventive behaviors. Findings indicate that individuals with higher health literacy are more likely to engage in health-promoting behaviors, utilize healthcare services, and effectively manage chronic diseases. In contrast, those with lower health literacy experience higher health risks due to limited access to and understanding of health information. The study highlights the effectiveness of community-based education programs, digital interventions, and culturally tailored strategies in improving health literacy. However, disparities persist, particularly among socioeconomically disadvantaged and migrant populations. Addressing these disparities requires targeted policies integrating health literacy into education systems, healthcare services, and public health initiatives. Future research should explore innovative interventions and standardized assessment tools to enhance the effectiveness of health literacy programs. Strengthening health literacy is essential for reducing health inequities, enhancing preventive care, and improving overall population health.